Economic studies of motherhood and childcare in South Africa - Hatch, Michelle (My University, 2018)
In this thesis, I examine the relationships between motherhood and childcare, and women’s wellbeing and economic status. South Africa is a particularly interesting country in which to explore these relationships given diverse family forms, a long history of labour migration and very low marriage rates particularly among African women. In the first empirical study (Chapter Two), I analyse the gender division of labour in physical and financial (paying for educational expenses) childcare. I show that women are more likely to be physical caregivers than men are financial caregivers. In South Africa, mothers are not always caregivers for their children and in African households, where mothers are more likely to be absent from the household, other women provide both physical and financial care to children. In the second study (Chapter Three), I explore the relationship among women, between their subjective wellbeing (SWB) and living with children. I examine if the nature of women’s caregiver status moderates this relationship, and whether caregiving itself is significantly associated with SWB. The results suggest that, in contrast to African women, motherhood and childcare is a less positive experience for non-African women. For African women, on average there is a positive association between physically caring for children (provided they receive help), and paying for the schooling of children. The positive relationship between physical care and SWB is stronger when women are looking after their own children. For non-African women, however, physical and financial care are negatively related to SWB with little difference between own and other children (which is not surprising given that relatively few non-African women are primary caregivers of other people’s children). In the final study (Chapter Four), I compare the economic status of mothers by their marital status and investigate the relationship between physical childcare and employment. I show that single mothers, on average, are economically disadvantaged compared to mothers who are married or cohabiting. Furthermore, there is a stronger negative association between providing primary physical care to children and being employed among single mothers. This is partly explained by single mothers who live away from their children being significantly less likely to be caregivers and more likely to be employed. Unlike married or cohabiting mothers, single mothers also do not receive more assistance with childcare when they transition into employment.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Economics School of Economic and Business Sciences, March, 2018
Keywords: Child care--South Africa; Child development--South Africa